2005
DOI: 10.1002/hyp.5617
|View full text |Cite
|
Sign up to set email alerts
|

Estimating shallow groundwater recharge in the headwaters of the Liverpool Plains using SWAT

Abstract: Abstract:A physically based catchment model (SWAT) was used for recharge estimation in the headwaters of the Liverpool Plains in NSW, Australia. The study used water balance modelling at the catchment scale to derive parameters for long-term recharge estimation. The derived parameters were further assessed at a subcatchment scale. Modelling results suggest that recharge occurs only in wet years, and is dominated by a few significant years or periods. The results were matched by independently observed bore data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 4 publications
3
30
0
Order By: Relevance
“…Deep cracks form an additional mechanism of deep evaporation that supports the chloride profiles and low water content in the matrix under vertisols. Sun and Cornish (2005) used SWAT to model runoff and groundwater recharge at the catchment scale (∼ 500 km 2 ) in a vertisolic catchment in eastern Australia. Considering water balances at this scale, they concluded that recharge models need to have a component that enables taking moisture out of the lower soil profile or groundwater during dry periods.…”
Section: Soil Cracks As Deep Evaporators and Unsaturated-zone Salinitymentioning
confidence: 99%
“…Deep cracks form an additional mechanism of deep evaporation that supports the chloride profiles and low water content in the matrix under vertisols. Sun and Cornish (2005) used SWAT to model runoff and groundwater recharge at the catchment scale (∼ 500 km 2 ) in a vertisolic catchment in eastern Australia. Considering water balances at this scale, they concluded that recharge models need to have a component that enables taking moisture out of the lower soil profile or groundwater during dry periods.…”
Section: Soil Cracks As Deep Evaporators and Unsaturated-zone Salinitymentioning
confidence: 99%
“…The SWAT model has been applied successfully throughout the world, for example in Asia (Hu et al, 2007;Ouyang et al, 2008;Somura et al, 2009), the USA (Ficklin et al, 2009), Europe (Panagopoulos et al, 2007), and other regions (Sun & Cornish, 2005;In the present study, we aimed to estimate the impacts of temperature change on discharge, sediment, nitrogen and phosphorus loads. We used SWAT and studied the NPS pollution from the land basin on the estuary under different temperature change scenarios for the lower Pearl River Delta.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the specific management objectives, placing more weight on some ecological attributes than on others and using optional sub-indices may be appropriate. At this point, the process becomes subjective and a logical decision framework can be used to solicit and document expert opinions (Smith et al, 2003). Weighting was not used in this study for integrated assessment.…”
Section: Watershed-health Index Formulationmentioning
confidence: 99%
“…Cook et al (2015) examined these relationships in five watersheds along the Virginia-Kentucky border and explored the effects of both the water quality and habitat on benthic macro-invertebrates by using data from a 3-year field study and Virginia Stream Condition Index (VSCI) scores to evaluate site-specific environmental variables (land use, habitat metrics, and water-quality parameters). Tango and Batiuk (2016) analyzed the interactions that affect the watershed and bay-water-quality recovery responses to management actions and a range of health conditions and impairments by measuring the physical, chemical, and biological parameters in Chesapeake Bay.…”
mentioning
confidence: 99%
See 1 more Smart Citation